-4x-2=-x-14

Simple and best practice solution for -4x-2=-x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-2=-x-14 equation:


Simplifying
-4x + -2 = -1x + -14

Reorder the terms:
-2 + -4x = -1x + -14

Reorder the terms:
-2 + -4x = -14 + -1x

Solving
-2 + -4x = -14 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-2 + -4x + x = -14 + -1x + x

Combine like terms: -4x + x = -3x
-2 + -3x = -14 + -1x + x

Combine like terms: -1x + x = 0
-2 + -3x = -14 + 0
-2 + -3x = -14

Add '2' to each side of the equation.
-2 + 2 + -3x = -14 + 2

Combine like terms: -2 + 2 = 0
0 + -3x = -14 + 2
-3x = -14 + 2

Combine like terms: -14 + 2 = -12
-3x = -12

Divide each side by '-3'.
x = 4

Simplifying
x = 4

See similar equations:

| 21+9x=5x-7 | | 5x-8-7x=12 | | a-90=371 | | -0.5[X-4]=1.5 | | (-6x^3+5x^2-8x+9)(17x^3+2x^2-4x-13)= | | In(3x-1)=1 | | x/182=4 | | (x-3)(x+3)-(x-4)(4+x)=2x | | 9j^2+12j-12=0 | | n^2=9n-8 | | -40-8v=6(8v+3)+2v | | 39/78=x/6 | | 7y-2y=2 | | log[6]4x^2-log[6]x=2 | | a/20=6 | | 9-9x=1-7x | | http://www.thelearningodyssey.com | | http://www.thelearningodyssey.com/Assess/DPT/QIEImagesStorage/HSLQ_/HSLQ_AI13C02_T_stem2_1.gif | | 8-3t=5t | | 8n-3(-7n-6)=-6+5n | | -05X-4=1.5 | | 16t^2+40t+20= | | 43+x=50 | | 2m^2+15=11m | | 18n^2+27n-5=0 | | b+34=19 | | 6(7+5x)=-6+6x | | 2(8x+8)=-4+6x | | 6*-2y=-4 | | (10x-2y)-(2x-7)= | | 46+x=58 | | 6+7xy= |

Equations solver categories